Definition of the Seabed in Navigation Routes Through Mud Areas - Kirby, R.; Parker, W. R.; van Oostrum, W. H. A. (The International Hydrographic Review, 2015)
Over most types of seabed the interface between the seabed sediment and the overlying sea water column is sharp and clearly identified by survey echo sounders. However, in areas with a large mobile population of cohesive sediment (mud), dense layers of suspended sediment occur which are intermediate in character between muddy seawater and the settled mud of the bed. Such suspensions (fluid mud) may create a surveying problem, owing to the multiple layering they produce on echo-sounder records. Echosounders alone do not allow an objective decision on which reflector should be regarded as the seabed for navigational purposes. A new technique has been devised involving detailed profiles of in situ density through the suspensions using gamma-ray densimeters. This information, together with knowledge o f ship behaviour in dense media, facilitates decisions on what values of in situ density should be defined as the seabed. A density value of 1.2 gm/cm3 is now used by the Netherlands Rijkswaterstaat to define the “Nautical Depth” since research has shown that suspensions of lower density do not significantly impede the passage of ships. In Europort sudden influxes of sediment during storms produce layers up to 3.0 m in thickness which are detected by echo-sounders, and once the presence of such a suspension resulted in the temporary closure of the port to supertanker navigation. However, density surveys reveal that on arrival these suspensions are of very low density and thus do not present a hazard to navigation. Density surveys are also used to guide the maintenance dredging fleet to areas where the 1.2 gm/cm3 density level is shallower than the nominated datum for the channel or to areas where consolidation has progressed to a point where high production is possible.